Anode, method for manufacturing anode, nonaqueous electrolyte storage element, method for manufacturing nonaqueous electrolyte storage element, and method for manufacturing nonaqueous electrolyte storage element
The use of a negative electrode with a coating layer containing a polyvalent metal imide salt or its reaction product with metal lithium addresses the issue of dendrite formation and short circuits in nonaqueous electrolyte storage devices, significantly improving their performance and durability.
Patent Information
- Application Number
- JP2021004937
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-01-15
Smart Images

Figure 0007665985000002 
Figure 0007665985000003 
Figure 0007665985000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, and a method for producing the same. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary battery generally has a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and is configured to charge and discharge by transferring ions between the electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used. Metallic lithium is known as a negative electrode active material having a high energy density and used in non-aqueous electrolyte storage elements (see Patent Documents 1 and 2). Patent Document 3 also describes a method of providing a protective film on the surface of metallic lithium using a fluorine-containing polymer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-100065 A [Patent Document 2] Japanese Patent Application Publication No. 07-245099 [Patent Document 3] JP 2003-36842 A Summary of the Invention [Problem to be solved by the invention]
[0004] In non-aqueous electrolyte storage elements using metallic lithium as the negative electrode active material, such as lithium batteries, metallic lithium may be deposited in a dendritic form on the surface of the negative electrode during charging (hereinafter, metallic lithium in a dendritic form will be referred to as "dendrite"). When this dendrite grows and penetrates the separator to come into contact with the positive electrode, it causes a micro-short circuit. For this reason, non-aqueous electrolyte storage elements containing metallic lithium as the negative electrode active material have the disadvantage that they are prone to micro-short circuits due to repeated charging and discharging. Even when a negative electrode provided with a protective film as in Patent Document 3 is used, the effect of suppressing the occurrence of micro-short circuits is not sufficient.
[0005] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide a negative electrode for a nonaqueous electrolyte storage element, which is capable of suppressing the occurrence of micro-short circuits, a nonaqueous electrolyte storage element, and methods for manufacturing the same. [Means for solving the problem]
[0006] One aspect of the present invention is a negative electrode for a nonaqueous electrolyte storage element, comprising: a negative electrode active material layer containing metallic lithium; and a coating layer that coats at least a portion of the negative electrode active material layer, the coating layer containing a polyvalent metal imide salt or a reaction product of the polyvalent metal imide salt and the metallic lithium.
[0007] Another aspect of the present invention is a method for producing a negative electrode for a nonaqueous electrolyte storage element, comprising contacting a negative electrode active material layer containing metallic lithium with a coating layer-forming material containing a polyvalent metal imide salt.
[0008] Another embodiment of the present invention is a nonaqueous electrolyte electricity storage element including the negative electrode according to the embodiment of the present invention.
[0009] Another aspect of the present invention is a method for producing a nonaqueous electrolyte storage element, comprising producing a nonaqueous electrolyte storage element using the negative electrode according to the aspect of the present invention or a negative electrode obtained by the method for producing a negative electrode according to the aspect of the present invention. Effect of the Invention
[0010] According to one aspect of the present invention, it is possible to provide a negative electrode for a nonaqueous electrolyte storage element, which is capable of suppressing the occurrence of micro-short circuits, a nonaqueous electrolyte storage element, and a method for producing the same. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is an external perspective view showing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] First, an outline of the negative electrode for a nonaqueous electrolyte storage element, the method for manufacturing the negative electrode for a nonaqueous electrolyte storage element, the nonaqueous electrolyte storage element, and the method for manufacturing the nonaqueous electrolyte storage element disclosed in this specification will be described.
[0013] A negative electrode for a nonaqueous electrolyte storage element according to one aspect of the present invention includes a negative electrode active material layer containing metallic lithium, and a coating layer that coats at least a portion of the negative electrode active material layer, the coating layer containing a polyvalent metal imide salt or a reaction product of the polyvalent metal imide salt and the metallic lithium.
[0014] The negative electrode can suppress the occurrence of micro-short circuit caused by repeated charging and discharging of the nonaqueous electrolyte storage element. That is, in the nonaqueous electrolyte storage element provided with the negative electrode, the occurrence of micro-short circuit caused by repeated charging and discharging is delayed. The reason is not clear, but the following reason is presumed. It is considered that at least a part of the polyvalent metal imide salt in the coating layer covers at least a part of the negative electrode active material layer, and by contacting the metallic lithium on the surface of the negative electrode active material layer, it reacts with the metallic lithium to form a reaction product. In addition, it is considered that this reaction proceeds even during charging and discharging of the nonaqueous electrolyte storage element. It is presumed that the coating layer that covers at least a part of the negative electrode active material layer contains a reaction product between such a polyvalent metal imide salt and metallic lithium, or is capable of forming such a reaction product, so that the coating layer becomes homogeneous and of good quality, and thus the growth of dendrites on the surface of the negative electrode is suppressed.
[0015] In some cases, it may be preferable for the coating layer to further contain a binder. When the coating layer further contains a binder, the polyvalent metal imide salt or the reaction product of the polyvalent metal imide salt and metallic lithium is sufficiently fixed to the negative electrode active material layer.
[0016] The binder is preferably a fluororesin. When the binder is a fluororesin, the coating layer becomes more uniform and of better quality, and the polyvalent metal imide salt used is more sufficiently fixed to the negative electrode active material layer, so that the occurrence of a micro-short circuit can be further suppressed.
[0017] In some cases, it may be preferable that the coating layer does not substantially contain a binder. In such a case, the coating layer containing the reaction product of the polyvalent metal imide salt and metallic lithium becomes more homogeneous and of good quality, and the coating layer has a low resistance, making it difficult for current concentration to occur, thereby making it possible to further suppress the occurrence of micro-short circuits. Note that, "the coating layer does not substantially contain a binder" means that the binder content in the coating layer is 1% by mass or less.
[0018] A method for producing a negative electrode for a nonaqueous electrolyte storage element according to one aspect of the present invention is a method for producing a negative electrode for a nonaqueous electrolyte storage element, comprising contacting a negative electrode active material layer containing metallic lithium with a coating layer-forming material containing a polyvalent metal imide salt.
[0019] According to this manufacturing method, it is possible to manufacture a negative electrode that can suppress the occurrence of micro-short circuits that occur due to repeated charging and discharging of a nonaqueous electrolyte electricity storage element.
[0020] A nonaqueous electrolyte electricity storage element according to one embodiment of the present invention is a nonaqueous electrolyte electricity storage element including a negative electrode according to one embodiment of the present invention.
[0021] The nonaqueous electrolyte storage element includes the negative electrode according to one aspect of the present invention, and therefore is prevented from causing micro-short circuits that occur during repeated charging and discharging.
[0022] A method for producing a nonaqueous electrolyte storage element according to one aspect of the present invention is a method for producing a nonaqueous electrolyte storage element, comprising producing a nonaqueous electrolyte storage element using a negative electrode according to one aspect of the present invention or a negative electrode obtained by the method for producing a negative electrode according to one aspect of the present invention.
[0023] According to this manufacturing method, a nonaqueous electrolyte electricity storage element can be manufactured in which the occurrence of micro-short circuits caused by repeated charging and discharging is suppressed.
[0024] Hereinafter, a negative electrode for a nonaqueous electrolyte storage element according to one embodiment of the present invention, a method for manufacturing a negative electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, and a method for manufacturing a nonaqueous electrolyte storage element will be described in order.
[0025] <Negative electrode for non-aqueous electrolyte storage element> A negative electrode for a non-aqueous electrolyte storage element according to one embodiment of the present invention includes a negative electrode substrate, a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer, and a coating layer that coats at least a portion of the negative electrode active material layer. That is, the negative electrode has a laminated structure in which at least three layers, the negative electrode substrate, the negative electrode active material layer, and the coating layer, are laminated in this order. The negative electrode active material layer and the coating layer may be laminated on only one surface of the negative electrode substrate, or may be laminated on both surfaces of the negative electrode substrate.
[0026] (Negative electrode substrate) The negative electrode substrate has electrical conductivity. The term "electrically conductive" means that the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 7 "Non-conductive" means that the volume resistivity is 10 7 It means that the resistance is more than Ω·cm. Metals such as copper, nickel, stainless steel, nickel-plated steel, etc., or alloys thereof are used as the material of the negative electrode substrate, and copper or copper alloys are preferred. The negative electrode substrate may be formed in the form of foil, vapor deposition film, etc., and foil is preferred from the viewpoint of cost. In other words, copper foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0027] The average thickness of the negative electrode substrate is preferably 2 μm or more and 35 μm or less, more preferably 3 μm or more and 30 μm or less, even more preferably 4 μm or more and 25 μm or less, and particularly preferably 5 μm or more and 20 μm or less. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate while increasing the energy density per volume of the nonaqueous electrolyte storage element. The "average thickness" refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of the substrate. The same applies to the "average thickness" of the positive electrode substrate described below.
[0028] (Middle class) The intermediate layer is a coating layer on the surface of the negative electrode substrate, and contains conductive particles such as carbon particles to reduce the contact resistance between the negative electrode substrate and the negative electrode active material layer. The configuration of the intermediate layer is not particularly limited, and can be formed, for example, from a composition containing a resin binder and conductive particles.
[0029] (Negative electrode active material layer) The negative electrode active material layer contains metallic lithium. The metallic lithium is a component that functions as a negative electrode active material. The metallic lithium may exist as pure metallic lithium substantially consisting of lithium alone, or may exist as a lithium alloy containing other metal components. Examples of the lithium alloy include a lithium silver alloy, a lithium zinc alloy, a lithium calcium alloy, a lithium aluminum alloy, a lithium magnesium alloy, and a lithium indium alloy. The lithium alloy may contain a plurality of metal elements other than lithium.
[0030] The negative electrode active material layer may be a layer consisting essentially of metallic lithium. The content of metallic lithium in the negative electrode active material layer may be 90% by mass or more, may be 99% by mass or more, or may be 100% by mass.
[0031] The negative electrode active material layer may be a lithium foil or a lithium alloy foil. The negative electrode active material layer may be a non-porous layer (solid layer). The negative electrode active material layer may also be a porous layer having particles containing metallic lithium. The average thickness of the negative electrode active material layer is preferably 5 μm to 1,000 μm, more preferably 10 μm to 500 μm, and even more preferably 30 μm to 300 μm.
[0032] (covering layer) The coating layer covers at least a part of the negative electrode active material layer. That is, the negative electrode active material layer may have an exposed part. However, the coating layer preferably covers 50% or more of the area of the outer surface (surface other than the surface in contact with the negative electrode base material or intermediate layer) of the negative electrode active material layer, more preferably covers 70% or more, and even more preferably covers 90% or more, and further preferably covers 99% or more.
[0033] The coating layer contains a polyvalent metal imide salt or a reaction product of the polyvalent metal imide salt and metallic lithium.
[0034] The metal element constituting the polyvalent metal imide salt is a metal element capable of forming a divalent or higher cation (polyvalent cation). The valence of the polyvalent cation of the metal element in the polyvalent metal imide salt may be divalent, trivalent, or quadrivalent or higher, but is preferably divalent or trivalent, and more preferably divalent.
[0035] Specific examples of polyvalent cations of metal elements include polyvalent cations of Group 2 elements (Mg 2+ , Ca 2+ , Sr 2+ , B.A. 2+ etc.), multivalent cations of group 3 elements (Sc 3+ , Y 3+ , La 3+ , Ce 3+ etc.), multivalent cations of group 4 elements (Ti 4+ etc., Zr 4+ ), multivalent cations of group 5 elements (V 5+ etc.), multivalent cations of group 6 elements (Cr 3+ etc.), polyvalent cations of group 7 elements (Mn 2+ etc.), multivalent cations of group 8 elements (Fe 2+ , Fe 3+ etc.), multivalent cations of group 9 elements (Co 2+ etc.), multivalent cations of group 10 elements (Ni 2+ etc.), multivalent cations of group 11 elements (Cu 2+ etc.), multivalent cations of group 12 elements (Zn 2+ , Cd 2+ etc.), polyvalent cations of metal elements in Group 13 (Al 3+ etc.), polyvalent cations of metal elements in Group 14 (Sn 2+ , Pb 2+ The polyvalent cations of metal elements may be used alone or in combination of two or more.
[0036] Among these, polyvalent cations of Group 2 or Group 3 elements are preferred, and polyvalent cations of Group 2 elements are more preferred. Among the polyvalent cations of Group 2 elements, magnesium ion (Mg 2+ ) and calcium ions (Ca 2+) is preferred, and calcium ion is more preferred. Among the polyvalent cations of Group 3 elements, lanthanide ions are preferred, and lanthanum ion (La 3+ ) is more preferred. Polyvalent cations of metal elements in the third to sixth periods are also preferred, and polyvalent cations of metal elements in the fourth, fifth or sixth periods are more preferred. When the coating layer contains polyvalent cations of such metal elements or metal elements derived from such polyvalent cations, the effect of suppressing the occurrence of micro-short circuits is enhanced.
[0037] The imide anion is N(SO2F)2 - (Bis(fluorosulfonyl)imide anion: FSI - ), N(CF3SO2)2 - (Bis(trifluoromethanesulfonyl)imide anion: TFSI - ), N(C2F5SO2)2 - (Bis(pentafluoroethanesulfonyl)imide anion: BETI - ), N(C4F9SO2)2 - (Bis(nonafluorobutanesulfonyl)imide anion), CF3-SO2-N-SO2-N-SO2CF3 - , FSO2-N-SO2-C4F9 - , CF3-SO2-N-SO2-C4F9 - , CF3-SO2-N-SO2-CF2-SO2-N-SO2-CF3 2- , CF3-SO2-N-SO2-CF2-SO3 2- , CF3-SO2-N-SO2-CF2-SO2-C(-SO2CF3)2 2- Sulfonylimide anions such as N(POF2)2 - Examples of the imide anion include phosphonylimide anions such as (bis(difluorophosphonyl)imide anion), and sulfonylimide anions are preferred. One or more types of imide anions can be used.
[0038] The imide anion preferably has a fluorine atom, and specifically, for example, a fluorosulfonyl group, a difluorophosphonyl group, a fluoroalkyl group, etc. As the imide anion, a sulfonylimide anion having a fluorine atom is more preferable, and a bis(trifluoromethanesulfonyl)imide anion (TFSI - ) is particularly preferred. By using such an imide anion, the coating layer can be made of better quality, and the occurrence of micro-short circuits can be further suppressed.
[0039] Specific examples of polyvalent metal imide salts include Mg(TFSI)2, Ca(TFSI)2, La(TFSI)3, Ti(TFSI)3, Mn(TFSI)2, Cu(TFSI)2, Zn(TFSI)2, Al(TFSI)3, Mg(FSI)2, Ca(FSI)2, La(FSI)3, Ti(FSI)3, Mn(FSI)2, Cu(FSI)2, Zn(FSI)2, Al(FSI)3, Ca(BETI)2, Ca[N(POF2)2]2, etc. One or more types of polyvalent metal imide salts can be used.
[0040] A part or all of the polyvalent metal imide salt used in forming the coating layer may be present in the coating layer as it is as a polyvalent metal imide salt. However, it is considered that the polyvalent metal imide salt reacts by contacting with the negative electrode active material layer containing metallic lithium. Therefore, a part or all of the polyvalent metal imide salt used in forming the coating layer may be present in the coating layer in the form of a reaction product between metallic lithium and the polyvalent metal imide salt.
[0041] The content of the metal element (or metal element of Groups 2 to 14) derived from the polyvalent metal imide salt in the coating layer is preferably 0.1% by mass to 50% by mass, more preferably 0.3% by mass to 30% by mass, and even more preferably 0.5% by mass to 20% by mass. By having the content of the metal element in the coating layer within the above range, the occurrence of micro-short circuit can be further suppressed.
[0042] The total content of the polyvalent metal imide salt and the reaction product of the polyvalent metal imide salt and metallic lithium in the coating layer may be 1% by mass or more and 100% by mass or less. The lower limit of the total content may be 5% by mass, 20% by mass, 50% by mass, 80% by mass, 90% by mass, 95% by mass, 99% by mass or 99.9% by mass. When the total content of the polyvalent metal imide and the reaction product of the polyvalent metal imide salt and metallic lithium in the coating layer is high, the coating layer formed becomes more homogeneous and good, and the occurrence of micro-short circuit may be more suppressed. The upper limit of the content may be 50% by mass or 30% by mass.
[0043] The coating layer may further contain a binder. Examples of the binder include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc. As the binder, fluororesins are preferred, and PVDF is more preferred.
[0044] When the coating layer contains a binder, the content of the binder in the coating layer is, for example, preferably 10% by mass or more and 99% by mass or less, and more preferably 50% by mass or more and 95% by mass or less. When the content of the binder in the coating layer is in the above range, the polyvalent metal imide salt and the like are sufficiently fixed to the negative electrode active material layer.
[0045] The binder content in the coating layer may be preferably 30% by mass or less, 10% by mass or less, 1% by mass or less, 0.1% by mass or less, or even 0% by mass. In addition, it may be preferable that the coating layer does not substantially contain a binder. The lower the binder content, the more homogeneous and high-quality the coating layer becomes, and the lower the resistance of the coating layer makes it difficult for current concentration to occur, so that the occurrence of micro-short circuit tends to be more suppressed.
[0046] The coating layer may not substantially contain a crosslinked polymerizable compound. In the negative electrode, even if the coating layer does not substantially contain a crosslinked polymerizable compound, the use of a polyvalent metal imide salt can suppress the occurrence of micro-short circuiting accompanying repeated charging and discharging of the nonaqueous electrolyte storage element. The content of the crosslinked polymerizable compound in the coating layer may be preferably 10% by mass or less, more preferably 3% by mass or less, 1% by mass or less, or 0% by mass. By setting the content of the crosslinked polymerizable compound in the coating layer to the above upper limit or less, productivity can be increased and production costs can be suppressed.
[0047] <Method of manufacturing a negative electrode for a non-aqueous electrolyte storage element> A method for producing a negative electrode for a non-aqueous electrolyte storage element according to one embodiment of the present invention includes, for example, laminating a negative electrode active material layer containing metallic lithium on a negative electrode substrate directly or via an intermediate layer (step 1), and contacting the negative electrode active material layer with a coating layer-forming material containing a polyvalent metal imide salt (step 2).
[0048] The above step 1 can be carried out by a conventionally known method. Specifically, for example, the negative electrode active material layer containing metallic lithium can be laminated on the negative electrode substrate directly or via an intermediate layer, and pressed. The negative electrode active material layer containing metallic lithium can be a lithium foil or a lithium alloy foil.
[0049] In the above step 2, a material for forming a coating layer is brought into contact with the exposed surface of the negative electrode active material layer in the laminate of the negative electrode base material and the negative electrode active material layer obtained in the above step 1. The material for forming a coating layer usually further contains a dispersion medium in addition to the polyvalent metal imide salt, and may further contain a binder.
[0050] The content of the polyvalent metal imide salt in the solid content (components other than the dispersion medium) in the coating layer forming material may be 1% by mass or more and 100% by mass or less. The content of the binder in the solid content (components other than the dispersion medium) in the coating layer forming material may be 0% by mass or more and 99% by mass or less.
[0051] As the dispersion medium of the material for forming the coating layer, an organic solvent such as N-methylpyrrolidone (NMP), toluene, etc. is preferably used. The content of the dispersion medium in the material for forming the coating layer is, for example, preferably 50% by mass or more and 99% by mass or less, more preferably 80% by mass or more and 96% by mass or less.
[0052] Specifically, the above step 2 can be carried out by the following procedure. A polyvalent metal imide salt, a dispersion medium, etc. are mixed to prepare a material for forming a coating layer. The prepared material for forming a coating layer is brought into contact with the surface of the negative electrode active material layer. The negative electrode active material layer (a laminate of a negative electrode active material layer and a film of a material for forming a coating layer) in contact with the material for forming a coating layer is dried. The material for forming a coating layer can be brought into contact with the negative electrode active material layer by applying the material for forming a coating layer or immersing the negative electrode active material layer in the material for forming a coating layer. Through these steps, a coating layer containing a polyvalent metal imide salt or a reaction product of the polyvalent metal imide salt and metallic lithium is laminated on the surface of the negative electrode active material layer.
[0053] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element according to one embodiment of the present invention has a positive electrode, a negative electrode, and a nonaqueous electrolyte. Hereinafter, a nonaqueous electrolyte secondary battery (hereinafter, simply referred to as a "secondary battery") will be described as an example of a nonaqueous electrolyte storage element. The positive electrode and the negative electrode are usually stacked or wound alternately with a separator interposed therebetween to form an electrode body. This electrode body is housed in a container, and the container is filled with a nonaqueous electrolyte. The nonaqueous electrolyte is interposed between the positive electrode and the negative electrode. In addition, as the container, a known metal container, a resin container, or the like that is usually used as a container for a secondary battery can be used.
[0054] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The intermediate layer of the positive electrode may have the same structure as the intermediate layer of the negative electrode.
[0055] The positive electrode substrate can be configured in the same manner as the negative electrode substrate, but the material used is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum and aluminum alloys are preferred in terms of the balance between potential resistance, high conductivity, and cost. In other words, aluminum foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloys include A1085P and A3003P as specified in JIS-H-4000 (2014).
[0056] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the secondary battery.
[0057] The positive electrode active material layer is a layer formed from a so-called positive electrode mixture containing a positive electrode active material. The positive electrode mixture forming the positive electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as necessary.
[0058] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Co 1-x-γ ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co 1-x ]O2(0≦x<0.5), Li[Li x Ni γ Mn1-x-γ ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co 1-x-γ-β ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al 1-x-γ-β ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn 2-γ O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.
[0059] The positive electrode active material is preferably a lithium transition metal composite oxide, more preferably a lithium transition metal composite oxide having an α-NaFeO2 crystal structure. The lithium transition metal composite oxide preferably contains nickel or manganese as a transition metal, more preferably both nickel and manganese. The lithium transition metal composite oxide may further contain other transition metals such as cobalt. In the lithium transition metal composite oxide having an α-NaFeO2 crystal structure, the molar ratio (Li / Me) of lithium (Li) to the transition metal (Me) is preferably more than 1, more preferably 1.1 or more, and even more preferably 1.2 or more. By using such a lithium transition metal composite oxide, the electric capacity can be increased. In addition, in the case of a nonaqueous electrolyte storage element using such a positive electrode active material, there is a tendency for it to be used at a high current density, and dendrites are usually easy to grow. Therefore, in the case of a nonaqueous electrolyte storage element having a positive electrode having the above-mentioned lithium transition metal composite oxide, the effect of suppressing the occurrence of a micro-short circuit can be more significantly enjoyed. In addition, the upper limit of the molar ratio (Li / Me) of lithium to the transition metal is preferably 1.6, more preferably 1.5.
[0060] As the lithium transition metal composite oxide having an α-NaFeO2 type crystal structure, a compound represented by the following formula (1) is preferable. Li 1+α Me 1-α O2···(1) In formula (1), Me is a transition metal including Ni or Mn, and 0<α<1.
[0061] In formula (1), Me preferably contains Ni and Mn. Me preferably consists essentially of two elements, Ni and Mn, or three elements, Ni, Mn, and Co. Me may contain other transition metals.
[0062] In formula (1), the lower limit of the molar ratio of Ni to Me (Ni / Me) is preferably 0.1, more preferably 0.2. On the other hand, the upper limit of this molar ratio (Ni / Me) is preferably 0.5, more preferably 0.45. By setting the molar ratio (Ni / Me) within the above range, the energy density is improved.
[0063] In formula (1), the lower limit of the molar ratio of Mn to Me (Mn / Me) is preferably 0.5, more preferably 0.55. On the other hand, the upper limit of this molar ratio (Mn / Me) is preferably 0.75, more preferably 0.7. By setting the molar ratio (Mn / Me) in the above range, the energy density is improved.
[0064] In formula (1), the upper limit of the molar ratio of Co to Me (Co / Me) is preferably 0.3, more preferably 0.2. The molar ratio (Co / Me) or the lower limit of the molar ratio (Co / Me) may be 0.
[0065] In formula (1), the molar ratio of Li to Me (Li / Me), i.e., (1+α) / (1-α), is preferably greater than 1.0 (α>0), more preferably 1.1 or more, and even more preferably 1.2 or more. On the other hand, the upper limit of this molar ratio (Li / Me) is preferably 1.6, more preferably 1.5. By setting the molar ratio (Li / Me) in the above range, the discharge capacity is increased.
[0066] The lower limit of the content of the lithium transition metal composite oxide relative to all the positive electrode active materials is preferably 50 mass%, more preferably 80 mass%, and even more preferably 95 mass%. The content of the lithium transition metal composite oxide relative to all the positive electrode active materials may be 100 mass%.
[0067] The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. Here, the "average particle size" refers to a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).
[0068] In order to obtain particles of the positive electrode active material in a predetermined shape, a pulverizer, a classifier, etc. are used. As a pulverization method, for example, a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve, etc. can be used. When pulverizing, wet pulverization in which water or an organic solvent such as hexane is coexistent can also be used. As a classification method, a sieve, a wind classifier, etc. are used as necessary for both dry and wet methods.
[0069] The content of the positive electrode active material in the positive electrode active material layer is preferably 70% by mass to 98% by mass, more preferably 80% by mass to 97% by mass, and even more preferably 90% by mass to 96% by mass. By setting the content of the positive electrode active material in the above range, the electric capacity of the secondary battery can be increased.
[0070] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, and conductive ceramics. Examples of carbonaceous materials include graphite and carbon black. Examples of carbon black include furnace black, acetylene black, and ketjen black. Among these, carbonaceous materials are preferred from the viewpoint of electrical conductivity and coating properties. Among these, acetylene black and ketjen black are preferred. Examples of the shape of the conductive agent include powder, sheet, and fiber.
[0071] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % or more and 40 mass % or less, and more preferably 2 mass % or more and 10 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.
[0072] Specific examples of the binder include the binders mentioned above as components of the coating layer of the negative electrode.
[0073] The content of the binder in the positive electrode active material layer is preferably from 0.5% by mass to 10% by mass, more preferably from 1% by mass to 6% by mass. By setting the content of the binder in the above range, the active material can be stably held.
[0074] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. In addition, when the thickener has a functional group that reacts with lithium, it is preferable to deactivate this functional group in advance by methylation or the like. In one embodiment of the present invention, it may be preferable that the thickener is not contained in the positive electrode active material layer.
[0075] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. In one embodiment of the present invention, it may be preferable that the filler is not contained in the positive electrode active material layer.
[0076] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0077] (Negative electrode) The negative electrode of the nonaqueous electrolyte storage element according to one embodiment of the present invention is the negative electrode described above as the negative electrode for the nonaqueous electrolyte storage element according to one embodiment of the present invention.
[0078] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.
[0079] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C in the atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C in the atmosphere. Examples of materials that have a mass loss of a predetermined amount or less when heated include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.
[0080] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0081] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polyethylene carbonate, polypropylene carbonate, polyvinyl carbonate, polyalkyl methacrylates such as polymethyl methacrylate, polyalkyl acrylates such as polymethyl acrylate, polyvinyl ethylene carbonate, polyvinyl acetate, polyvinylpyrrolidone, polymaleic acid and its derivatives, polyvinylidene fluoride, poly(vinylidene fluoride-co-hexafluoropropylene), polytetrafluoroethylene, etc. Copolymers containing two or more of the monomers constituting the above-mentioned polymers may be used, or a mixture of two or more polymers may be used. These polymers may also be combined with inorganic salts or ionic liquids. The use of a polymer gel has the effect of suppressing leakage. As the separator, a polymer gel may be used in combination with the porous resin film or nonwoven fabric as described above.
[0082] (Non-aqueous electrolyte) As the non-aqueous electrolyte, a non-aqueous electrolytic solution containing a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent is preferably used.
[0083] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.
[0084] As the non-aqueous solvent, it is preferable to use at least one of a cyclic carbonate and a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When a cyclic carbonate and a chain carbonate are used in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.
[0085] Examples of the cyclic carbonate include ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, vinylethylene carbonate, chloroethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, fluoromethylethylene carbonate, trifluoroethylethylene carbonate, styrene carbonate, catechol carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. The number of carbon atoms in the cyclic carbonate may be, for example, 3 or more and 13 or less, or 7 or less, or 5 or less.
[0086] As the cyclic carbonate, from the standpoint of oxidation resistance and the like, fluorinated cyclic carbonates such as fluoroethylene carbonate, difluoroethylene carbonate, fluoromethylethylene carbonate, and trifluoroethylethylene carbonate are preferred.
[0087] Examples of the chain carbonate include diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diphenyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, bis(2,2,2 trifluoroethyl) carbonate, ethyl 2,2,2 trifluoroethyl carbonate, etc. The number of carbon atoms in the chain carbonate may be, for example, 3 or more and 13 or less, or 7 or less, or 5 or less.
[0088] As the chain carbonate, from the viewpoint of oxidation resistance and the like, fluorinated chain carbonates such as 2,2,2-trifluoroethyl methyl carbonate, bis(2,2,2 trifluoroethyl) carbonate, and ethyl 2,2,2 trifluoroethyl carbonate are preferred.
[0089] The content of the carbonate relative to the total non-aqueous solvent is preferably 50 vol % or more and 100 vol % or less, more preferably 80 vol % or more, and in some cases further preferably 90 vol % or more, 95 vol % or more, or 99 vol % or more.
[0090] The non-aqueous solvent preferably contains a fluorinated solvent. The total content of the fluorinated solvent with respect to the total non-aqueous solvent is preferably 60% by volume or more, more preferably 90% by volume or more, even more preferably 99% by volume or more, and particularly preferably 100% by volume. The fluorinated solvent refers to a solvent (non-aqueous solvent) having a fluorine atom in the molecule, such as a fluorinated carbonate (a fluorinated linear carbonate and a fluorinated cyclic carbonate), a fluorinated ether, etc. In this way, by containing a fluorinated solvent, preferably by containing it at the above-mentioned lower limit or more, it is possible to further improve the suppression of micro-short circuit, oxidation resistance, etc.
[0091] The electrolyte salt is usually a lithium salt. Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, and lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred. In addition, from the viewpoint of oxidation resistance, the electrolyte salt preferably contains a fluorine atom.
[0092] The content of the electrolyte salt in the non-aqueous electrolyte is 0.1 mol / dm 3 More than 2.5mol / dm 3 Less than 0.3 mol / dm is preferred. 3 More than 2.0mol / dm 3Less than 0.5 mol / dm is more preferable. 3 More than 1.7mol / dm 3 More preferably, 0.7 mol / dm 3 More than 1.5mol / dm 3 The following is particularly preferable: By setting the content of the electrolyte salt within the above range, the ionic conductivity of the non-aqueous electrolyte can be increased.
[0093] The non-aqueous electrolyte may contain an additive, such as aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, and sulfuric acid. Examples of the additives include dimethyl, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, etc. These additives may be used alone or in combination of two or more.
[0094] The content of the additive in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive in the above range, it is possible to improve the capacity retention performance or the charge / discharge cycle performance after high-temperature storage, and to further improve safety.
[0095] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.
[0096] The solid electrolyte can be selected from any material that has ionic conductivity such as lithium, sodium, calcium, etc., and is solid at room temperature (e.g., 15° C. to 25° C.). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, oxynitride solid electrolytes, polymer solid electrolytes, etc.
[0097] As the sulfide solid electrolyte, in the case of a lithium ion secondary battery, for example, Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 etc.
[0098] In the non-aqueous electrolyte storage element, the positive electrode potential at the end of charge voltage during normal use is 4.30 V vs. Li / Li + It is preferable that the value is 4.35V vs. Li / Li or more. + More preferably, it is 4.40V vs. Li / Li or more. + By setting the positive electrode potential at the end-of-charge voltage during normal use to the above lower limit or higher, it is possible to increase the discharge capacity and the energy density.
[0099] In addition, "normal use" refers to a case where the nonaqueous electrolyte storage element is used under charging conditions recommended or specified for the nonaqueous electrolyte storage element. For example, if a charger for the nonaqueous electrolyte storage element is provided, the "normal use" refers to a case where the nonaqueous electrolyte storage element is used using the charger.
[0100] The upper limit of the positive electrode potential at the end-of-charge voltage during normal use of the nonaqueous electrolyte storage element is, for example, 5.0 V vs. Li / Li + 4.8V vs. Li / Li + 4.7V vs. Li / Li + It may be.
[0101] Dendrites tend to grow easily when the current density during charging is high. Therefore, the nonaqueous electrolyte electricity storage element according to one embodiment of the present invention can be suitably applied to applications in which charging is performed at a high current density. Examples of such applications include power sources for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs), and power sources for charging regenerative power.
[0102] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.
[0103] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0104] <Configuration of Nonaqueous Electrolyte Electricity Storage Device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology according to one embodiment of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit.
[0105] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.
[0106] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> A method for producing a nonaqueous electrolyte storage element according to one embodiment of the present invention includes producing a nonaqueous electrolyte storage element using a negative electrode according to one embodiment of the present invention or a negative electrode obtained by a method for producing a negative electrode according to one embodiment of the present invention. The production method can be performed in the same manner as in the production of a conventionally known nonaqueous electrolyte storage element, except that a negative electrode according to one embodiment of the present invention or a negative electrode obtained by a method for producing a negative electrode according to one embodiment of the present invention is used as the negative electrode.
[0107] For example, a method for producing the nonaqueous electrolyte storage element includes preparing or producing a positive electrode, preparing or producing a negative electrode, preparing or preparing a nonaqueous electrolyte, preparing or producing a separator, laminating or winding the positive electrode and the negative electrode with the separator interposed therebetween to form an electrode assembly in which the positive electrode and the negative electrode (electrode assembly) are alternately stacked, housing the positive electrode and the negative electrode (electrode assembly) in a container, and injecting the nonaqueous electrolyte into the container. After injection, the injection port is sealed to obtain the nonaqueous electrolyte storage element.
[0108] <Other embodiments> The present invention is not limited to the above-described embodiments, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0109] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (lithium battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The nonaqueous electrolyte storage element of the present invention can also be applied to various nonaqueous electrolyte secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors. The nonaqueous electrolyte storage element of the present invention can also be applied to lithium-air batteries. EXAMPLES
[0110] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0111] [Example 1] (Preparation of positive electrode) The positive electrode active material has an α-NaFeO2 type crystal structure and Li 1+α Me 1-α A lithium transition metal composite oxide represented by O2 (Me is a transition metal) was used. Here, the molar ratio of Li to Me, Li / Me, was 1.33, and Me was composed of Ni and Mn, and was contained in a molar ratio of Ni:Mn=1:2.
[0112] A positive electrode mixture paste was prepared using N-methylpyrrolidone (NMP) as a dispersion medium, containing the positive electrode active material, acetylene black (AB) as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio of 94:4.5:1.5 as solid contents. The positive electrode mixture paste was applied to one side of an aluminum foil as a positive electrode substrate, dried, and pressed to prepare a positive electrode with a positive electrode active material layer. The positive electrode had a current density of 5.1 mA / cm at 1 C. 2 It was designed and manufactured to be.
[0113] (Preparation of negative electrode) The nickel lead wire was sandwiched between two lithium foils (metallic lithium 100% by mass) with an average thickness of 300 μm as the negative electrode active material layer. A material for forming a coating layer was prepared by mixing a polyvalent metal imide salt Ca(TFSI)2 as an imide salt, a binder PVDF, and a dispersion medium NMP in a mass ratio of 0.05:0.5:6.5. This was heated at 45°C, applied to the surface of the lithium foil, and then dried to prepare a negative electrode in which a coating layer was laminated on the surface of the negative electrode active material layer containing metallic lithium.
[0114] (Preparation of non-aqueous electrolyte) Fluoroethylene carbonate (FEC) and 2,2,2-trifluoroethyl methyl carbonate (TFEMC) were mixed in a volume ratio of 30:70, and LiPF6 was added at 1 mol / dm 3 to give a non-aqueous electrolyte.
[0115] (Preparation of non-aqueous electrolyte storage element) The positive electrode and the negative electrode were laminated with a separator made of a microporous polyolefin film interposed therebetween to produce an electrode assembly. The electrode assembly was placed in a container made of a metal resin composite film, and the nonaqueous electrolyte was poured into the container, which was then sealed by heat welding to obtain the nonaqueous electrolyte storage element (lithium battery) of Example 1.
[0116] [Examples 2 to 6 and Comparative Examples 1 to 3] A material for forming a coating layer was prepared using the types of imide salt and binder as shown in Table 1, and the negative electrodes and nonaqueous electrolyte storage elements of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that this material for forming a coating layer was used. In Examples 4 to 6, a negative electrode in which a coating layer was formed using a material for forming a coating layer that did not contain a binder was used to obtain a nonaqueous electrolyte storage element. In Comparative Example 1, a negative electrode in which a coating layer consisting of only a binder was formed using a material for forming a coating layer that did not contain an imide salt was used to obtain a nonaqueous electrolyte storage element.
[0117] (Initial charge / discharge) The obtained nonaqueous electrolyte storage element was initially charged and discharged under the following conditions. At 25°C, constant current and constant voltage charging was performed with a current of 0.1C and a charge end voltage of 4.6V. The charge end condition was that the current was 0.05C. Then, a rest period of 10 minutes was provided. Then, constant current discharging was performed with a current of 0.1C and a discharge end voltage of 2.0V, and then a rest period of 10 minutes was provided. This charge and discharge cycle was performed for two cycles.
[0118] (Charge-discharge cycle test) Next, the following charge-discharge cycle test was performed. At 25°C, constant current and constant voltage charging was performed with a current of 0.2C and a charge end voltage of 4.6V. The charge end condition was that the current was until 0.05C. After that, a rest period of 10 minutes was provided. Then, constant current discharging was performed with a current of 0.1C and a discharge end voltage of 2.0V, and then a rest period of 10 minutes was provided. This charge-discharge cycle was repeated, and the number of cycles until a micro-short circuit occurred was recorded. The results (number of cycles until a micro-short circuit occurred) are shown in Table 1.
[0119] [Table 1]
[0120] As shown in Table 1, the nonaqueous electrolyte storage elements of Examples 1 to 6, in which a negative electrode in which a coating layer was formed using a coating layer-forming material containing a polyvalent metal imide salt was used, had a cycle number of 78 or more times until a micro-short circuit occurred, and a high micro-short circuit occurrence suppression effect was confirmed. Among the examples, the nonaqueous electrolyte storage elements of Examples 4 to 6, which have a negative electrode in which a coating layer not containing a binder was formed using a coating layer-forming material containing no binder, were confirmed to have a particularly excellent micro-short circuit occurrence suppression effect. On the other hand, the nonaqueous electrolyte storage elements of Comparative Examples 2 and 3, in which a negative electrode in which a coating layer was formed using a coating layer-forming material containing a monovalent metal imide salt was used, had a cycle number of about the same or less until a micro-short circuit occurred compared to the nonaqueous electrolyte storage element of Comparative Example 1 in which a negative electrode in which a coating layer was formed using a coating layer-forming material containing no imide salt was used, and no micro-short circuit occurrence suppression effect was observed. [Industrial Applicability]
[0121] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]
[0122] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device
Claims
1. a negative electrode active material layer containing metallic lithium; a coating layer that covers at least a portion of the negative electrode active material layer; Equipped with the coating layer comprises a polyvalent metal imide salt or a reaction product of the polyvalent metal imide salt and the metallic lithium, The negative electrode for a non-aqueous electrolyte storage element, wherein the coating layer further contains a binder.
2. A negative electrode active material layer containing metallic lithium; a coating layer that covers at least a portion of the negative electrode active material layer; Equipped with the coating layer comprises a polyvalent metal imide salt or a reaction product of the polyvalent metal imide salt and the metallic lithium, the cation of the metal element constituting the polyvalent metal imide salt is a polyvalent cation of a metal element of the third to fifth periods; a negative electrode for a nonaqueous electrolyte storage element, wherein the total content of the polyvalent metal imide salt and the reaction product in the coating layer is from 50% by mass to 100% by mass;
3. A negative electrode active material layer containing metallic lithium; a coating layer that covers at least a portion of the negative electrode active material layer; Equipped with the coating layer comprises a polyvalent metal imide salt or a reaction product of the polyvalent metal imide salt and the metallic lithium, the cation of the metal element constituting the polyvalent metal imide salt is a polyvalent cation of a Group 3 element, The anions constituting the polyvalent metal imide salts are N(SO 2 F) 2 - , N(CF 3 SO 2 ) 2 - , N(C 2 F 5 SO 2 ) 2 - , N(C 4 F 9 SO 2 ) 2 - , CF 3 -SO 2 -N-SO 2 -N-SO 2 CF 3 - , FSO 2 -N-SO 2 -C 4 F 9 - , CF 3 -SO 2 -N-SO 2 -C 4 F 9 - , CF 3 -SO 2 -N-SO 2 -CF 2 -SO 2 -N-SO 2 -CF 3 2 - , CF 3 -SO 2 -N-SO 2 -CF 2 -SO 3 2 - , CF 3 —SO 2 —N—SO 2 —CF 2 —SO 2 —C(—SO 2 CF 3 ) 2 2− or N(POF 2 ) 2 − .
4. 2. The negative electrode according to claim 1, wherein the binder is a fluororesin.
5. 4. The negative electrode according to claim 2, wherein the coating layer is substantially free of a binder.
6. 6. The method for producing the negative electrode according to claim 1, further comprising contacting a coating layer-forming material containing a polyvalent metal imide salt with a negative electrode active material layer containing metallic lithium.
7. A nonaqueous electrolyte storage element comprising the negative electrode according to claim 1 .
8. A positive electrode having a positive electrode active material; a negative electrode having a negative electrode active material layer containing metallic lithium and a coating layer that coats at least a portion of the negative electrode active material layer; the coating layer comprises a polyvalent metal imide salt or a reaction product of the polyvalent metal imide salt and the metallic lithium, A nonaqueous electrolyte storage element in which the cation of the metal element constituting the polyvalent metal imide salt is a polyvalent cation of a metal element of the third to fifth periods (excluding the case where the positive electrode active material contains a compound represented by the following formula (1) having a crystal structure belonging to the space group FM3-M: Li x Me y O α F β ... (1) (Me is one or more elements selected from the group consisting of Mn, Co, Ni, Fe, Al, B, Ce, Si, Zr, Nb, Pr, Ti, W, Ge, Mo, Sn, Bi, Cu, Mg, Ca, Ba, Sr, Y, Zn, Ga, Er, La, Sm, Yb, V, and Cr, and satisfies 1.7≦x≦2.2, 0.8≦y≦1.3, 1≦α≦2.5, and 0.5≦β≦2).
9. A method for producing a nonaqueous electrolyte storage element, comprising: producing a nonaqueous electrolyte storage element using the negative electrode according to claim 1 or 3.
10. A method for manufacturing a non-aqueous electrolyte storage element, comprising producing a non-aqueous electrolyte storage element using the negative electrode described in claim 2.
Citation Information
Patent Citations
Negative electrode for nonaqueous electrolyte type lithium secondary battery
JP1995245099A
Electrolyte for battery, and nonaqueous electrolyte battery
JP2002231306A
Manufacturing method of lithium metal anode protective coat for lithium battery
JP2003036842A
Electrolyte for secondary battery and secondary battery using it
JP2004253296A
Electrolyte solution and battery
JP2007257961A